2010
DOI: 10.1089/hum.2009.134
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Integration Site Preferences of an HIV-1-Based Vector by Expression of a Novel Synthetic Protein

Abstract: HIV-1-based lentiviral vectors are a promising tool for gene therapy. However, integration of a lentiviral vector into host cell genes may lead to the development of cancer. Therefore, control of integration site selection is critical to the successful outcome of gene therapy approaches that use these vectors. The discovery that integration site selection by HIV-1 and HIV-1-based vectors is controlled by the LEDGF=p75 protein has presented new opportunities to control integration site selection. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 49 publications
(62 reference statements)
3
50
0
Order By: Relevance
“…Cells depleted for LEDGF/p75 (13,14) or somatic knock-out cells (15,16) inhibit productive HIV infection. In addition, fusion proteins in which the LEDGF/p75 DNA binding portion is replaced with an alternative chromatin binding domain efficiently tether the PIC to the host cell chromatin and support lentiviral vector transduction (17)(18)(19)(20). We and others demonstrated that these fusion proteins retarget proviral integration to the regions bound by the specific chromatin binding domain (17,18).…”
mentioning
confidence: 95%
“…Cells depleted for LEDGF/p75 (13,14) or somatic knock-out cells (15,16) inhibit productive HIV infection. In addition, fusion proteins in which the LEDGF/p75 DNA binding portion is replaced with an alternative chromatin binding domain efficiently tether the PIC to the host cell chromatin and support lentiviral vector transduction (17)(18)(19)(20). We and others demonstrated that these fusion proteins retarget proviral integration to the regions bound by the specific chromatin binding domain (17,18).…”
mentioning
confidence: 95%
“…In cells depleted of LEDGF/p75, HIV-1 integration and replication were significantly affected, while the residual HIV-1 integration sites were less enriched in transcriptional units (30-32). Furthermore, it was possible to retarget HIV-1 integration by chimeric proteins containing the IN binding domain (IBD) of LEDGF/p75 and alternative chromatin binding domains (33)(34)(35).Several cellular proteins, including transcription factors and chromatin and RNA binding proteins, were recently identified as potential interaction partners for MLV IN (36). This diverse group of proteins included BRD2, a member of the bromodomain and extraterminal domain (BET) family of chromatin binding…”
mentioning
confidence: 99%
“…In cells depleted of LEDGF/p75, HIV-1 integration and replication were significantly affected, while the residual HIV-1 integration sites were less enriched in transcriptional units (30-32). Furthermore, it was possible to retarget HIV-1 integration by chimeric proteins containing the IN binding domain (IBD) of LEDGF/p75 and alternative chromatin binding domains (33)(34)(35).…”
mentioning
confidence: 99%
“…LEDGF/p75 has a C-terminally located IN-binding domain (IBD) (24,25) and N-terminal elements that bind chromatin (26,27). Novel fusion proteins comprising the LEDGF/p75 IBD and foreign chromatin binding domains redirect HIV-1 to integrate at positions where the heterologous binding partner preferentially binds, demonstrating a direct role for the host factor in targeting lentiviral integration (28)(29)(30). Neither the preference for the local DNA sequence at the site of HIV-1 integration (20)(21)(22) nor the preference for gene-dense regions of chromosomes (12,20) seems to be influenced by LEDGF/p75.…”
mentioning
confidence: 99%